Cortical post-movement and sensory processing disentangled by temporary deafferentation - Thiemann, Ulf; Resch, Franz; Weisbrod, Matthias; Bender, Stephan (NeuroImage, 2012)
Motor system calibration depends crucially on the adjustment to the consequences of a movement, which often occur when the movement itself is already completed. The mechanisms by which reafferent feedback information is compared to the programmed movement remain unclear. In the current study, the hypothesis of a short term memory trace in the motor cortex which outlasts quick movements and is generated independently from reafferent feedback was challenged by temporal deafferentation. Post-movement cortical potentials were recorded by high-resolution EEG during a reaction time task which required speeded unilateral right-hand or left-hand button presses. We analysed lateralized motor N700 (motor post-imperative negative variation), a post-movement component, under temporary deafferentation achieved through application of a blood pressure tourniquet in ten healthy adult subjects. Motor N700 persisted under deafferentation in the absence of reafferent tactile and proprioceptive feedback input into the sensorimotor cortex, which was abolished under deafferentation. Source analysis pointed towards continuing activation in the pre-/primary motor cortex. Thus, motor post-processing can be dissociated from reafferent sensory feedback. Motor cortex activation outlasts quick movements for about a second also in the absence of a reafferent signal. Continuing motor cortex activation could act as an internal motor model in motor learning and allow better adjustment of movements according to the evaluation of their consequences.